Acute lung injury in preterm fetuses and neonates: mechanisms and molecular pathways. (November 2013) - Iliodromiti, Zoe; Zygouris, Dimitrios; Sifakis, Stavros; Pappa, Kalliopi I.; Tsikouras, Panagiotis; Salakos, Nikolaos; Daniilidis, Angelos; Siristatidis, Charalambos; Vrachnis, Nikolaos
Abstract Acute lung injury (ALI) results in high morbidity and mortality among preterm neonates and efforts have therefore been devoted to both antenatal and postnatal prevention of the disease. ALI is the result of an inflammatory response which is triggered by a variety of different mechanisms. It mostly affects the fetal lung and, in particular, causes damage to the integrity of the lung's alveolar-capillary unit while weakening its cellular linings. Chemotactic activity and inflammatory products, such as proinflammatory cytokines TNF-α, IL-1, IL-6, IL-11, VEGF, TGF-α and TGF-β, provoke serious damage to the capillary endothelium and the alveolar epithelium, resulting in hyaline membrane formation and leakage of protein-rich edema fluid into the alveoli. Chorioamnionitis plays a major part in triggering fetal lung inflammation, while mechanical ventilation, the application of which is frequently necessary in preterm neonates, also causes ALI by inducing proinflammatory cytokines. Many different ventilation-strategies have been developed in order to reduce potential lung injury. Furthermore, tissue injury may occur as a result of injurious oxygen by-products (Reactive Oxygen Species, ROS), secondary to hyperoxia. Knowledge of the inflammatory pathways that connect intra-amniotic inflammation and ALI can lead to the formulation of novel interventional procedures. Future research should concentrate on the pathophysiology of ALI in preterm neonates and οn possible pharmaceutical interventions targeting prevention and/or resolution of ALI.